1990
DOI: 10.3109/00365519009091602
|View full text |Cite
|
Sign up to set email alerts
|

Primary platelet activation in recent-onset type 1 diabetes mellitus

Abstract: Platelet function (as production of thromboxane B2 by platelets stimulated with collagen, and plasma beta-thromboglobulin) and thrombin activity (as plasma fibrinopeptide A) were investigated in eight young (mean age 27 +/- 3 SE years) male patients in which type 1 diabetes mellitus had been diagnosed 2 to 6 months previously. They were all in excellent stable metabolic control (mean HbA1c 5.6 +/- 0.4 SE %) and free from any complications. The haemostatic variables were assessed at rest and after cycloergometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, the finding of signs of platelet activation in animal models (33) and in young patients with uncomplicated IDDM of very recent onset (34) suggests an alternative, non-complication-dependent pathogenesis. The results of this study indicate that an unsatisfying metabolic control determines an increase of [Ca 2+ ]i in the platelets of IDDM patients.…”
Section: Conclusion-mentioning
confidence: 91%
“…However, the finding of signs of platelet activation in animal models (33) and in young patients with uncomplicated IDDM of very recent onset (34) suggests an alternative, non-complication-dependent pathogenesis. The results of this study indicate that an unsatisfying metabolic control determines an increase of [Ca 2+ ]i in the platelets of IDDM patients.…”
Section: Conclusion-mentioning
confidence: 91%
“…Platelet activation, the process of increased cell surface expression of binding receptors and release of vasoactive substances, has been shown at an early stage in diabetes and in insulin resistant states, [8][9][10] in the absence of overt cardiovascular disease, suggesting that this altered platelet activity may contribute to the subsequent development of vasculopathy. 11 Diabetes, insulin resistance and hyperglycaemia are all pro-coagulant states, [12][13][14][15] enhancing clot stability, increasing its propagation and inhibiting thrombus dissolution. 16 Enhanced expression of plasminogen activator inhibitor-1 (PAI-1) has been demonstrated in insulin resistance, 17 and down regulation of antithrombin III (ATIII) activity, by non-enzymatic glycosylation, has been shown to reduce its in vitro thrombin inhibiting activity.…”
Section: Mechanisms Of Increased Risk In Diabetes? (Figure 2) Platelementioning
confidence: 99%
“…Increased MPV may be the consequence of either increased platelet activation or a high number of large, hyperaggregable platelets [76]. Activated platelets react to activated leukocytes and endothelial cells through adhesion molecules connecting inflammation and thrombosis [77]. Hekimsoy et al demonstrated that there is no link between MPV and HbA1c (glycated haemoglobin), fasting blood glucose, patient age, or duration of diabetes, suggesting that an increase in MPV values may be due to the diabetic status alone [76].…”
Section: Fructosamine and Blood Countmentioning
confidence: 99%